The Role of Aspirin as Otoprotective Agent in Patients Receiving Amikacin Therapy - Mahdi, Estabraq M. (AL-Kindy College Medical Journal, 2011)
Objective: To investigate and prove that aspirin protects, or at least attenuates amikacin ototoxicity in humans. Method: This study was conducted in 60 patients that completed all requirements .The patients were divided into two groups: • Control group: receive placebo treatment. • Drug–treated group: They receive aspirin coated tablets (1.5gm/ day), 500mg 8 hourly. Both groups had similar aspects regarding the gender, age and weight. The duration of therapy was 7 days and dosage of amikacin was 1gm/day (500mg 12 hourly). Results: Comparison of Audiometry test in Ear/Nose/Throat (E.N.T.) Department (Pure Tone Audiometry) at 1000 Hertz (Hz), 2000 Hz, 4000 Hz, and 8000 Hz showed significant differences between mean Audiometry at 250Hz was significantly different only at 8th and 15th day while at the frequency of 500Hz the difference was significant at the 15thday only. Conclusion: In present study, we had shown that aspirin can protect the patients who are receiving amikacin therapy from it’ s ototoxicity.